Robotic thoracoscopic parathyroidectomy for ectopic mediastinal parathyroid adenoma - P. K. Yablonsky; A. S. Kuzmichev; E. V. Shepichev; A. L. Akinchev; Z. S. Matveeva (Вестник хирургии имени И.И. Грекова)
The publication presents the successful experience of using the DaVinci robotic system for the treatment of persistent hyperparathyroidism caused by mediastinal ectopic parathyroid adenoma in 62 years old female patient. The role of single photon emission computed tomography in diagnostics was demonstrated.